ADHD & Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The efficacy of methylphenidate (MPH) and clonidine (CLON), alone and in combination, in 136 children with attention deficit hyperactivity disorder (ADHD) and chronic tic disorder, was evaluated in a multicenter, randomized, double-blind clinical trial, and reported by the Tourette Syndrome Study Group from the University of Rochester, NY.